2019
DOI: 10.1093/mnras/stz2652
|View full text |Cite
|
Sign up to set email alerts
|

Can redshift errors bias measurements of the Hubble Constant?

Abstract: Redshifts have been so easy to measure for so long that we tend to neglect the fact that they too have uncertainties and are susceptible to systematic error. As we strive to measure cosmological parameters to better than 1% it is worth reviewing the accuracy of our redshift measurements. Surprisingly small systematic redshift errors, as low as 10 −4 , can have a significant impact on the cosmological parameters we infer, such as H 0 . Here we investigate an extensive (but not exhaustive) list of ways in which … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 38 publications
2
58
0
Order By: Relevance
“…For example, in Ref. [14], it was found that redshift uncertainties cannot account for the discrepancy, and, in Refs. [15][16][17], a similar conclusion was drawn with regard to the local Hubble flow.…”
Section: A the Hubble Tensionmentioning
confidence: 97%
“…For example, in Ref. [14], it was found that redshift uncertainties cannot account for the discrepancy, and, in Refs. [15][16][17], a similar conclusion was drawn with regard to the local Hubble flow.…”
Section: A the Hubble Tensionmentioning
confidence: 97%
“…Explanations for the tension between direct measurements and CMB estimates range from underestimated systematic errors or modeling of the primordial power spectrum (e.g., Davis et al 2019;Dhawan et al 2020;Anderson 2019;Hazra et al 2019), to models for dark energy (e.g., Li & Shafieloo 2019;Alestas et al 2020;Di Valentino et al 2020), to unmodeled pre-recombination physics that lead to a decreased sound horizon scale (e.g., Poulin et al 2019;Chiang & Slosar 2018;Beradze & Gogberashvili 2020;Vagnozzi 2019;Lin et al 2019;Arendse et al 2019). See Knox & Millea (2020) for a review of possible solutions to the tension.…”
Section: Bao and The H 0 Tensionmentioning
confidence: 99%
“…The expansion factors a, strictly proportional to the recession velocities, are calculated from a = 1/(1 + z) = ν/ν 0 and are not modified, since observational errors of redshift determinations are tiny compared to errors about D L . Though this has been recently contested if the reader carefully examines the data they will agree with our assessment of relative error [37].…”
Section: Hii and Gehr Datamentioning
confidence: 60%
“…Both measures are used for historical reasons, magnitude being related to luminosity as perceived by the human eye being approximately the log(luminosity). Some astronomers actually worry more about relatively minor redshift errors than investigate the larger distance errors [37]. Third, results and parameters from this type of analysis (pseudo-H-routine) are interesting and immediately useful in today's astrophysics.…”
Section: Conclusion and Discussionmentioning
confidence: 99%